A case of uneventful ABO-incompatible liver transplantation from a deceased donor managed with routine immunosuppressive treatment - Tümgör, Gökhan; Tuncer, Recep; Yıldızdaş, Dinçer; Ülkü, Abdullah; Akcam, Atılgan Tolga; Demiryürek, Haluk (Turkish Journal of Gastroenterology, 2014)
Abstract ABO-incompatible liver transplantation (ILT) was formerly contraindicated because of the increased risk of antibody-mediated humoral graft rejection due to preformed anti-A/-B antibodies on recipient endothelial cells. A 2.5-year-old girl with end-stage liver disease underwent cadaveric donation ILT because of acute liver failure and esophageal variceal bleeding before transplantation. The patient’s blood type was A Rh (−) and the donor’s blood type B Rh (+). The operation and postoperative course were uneventful. The immunosuppression consisted of steroids, and tacrolimus was initiated on the day of the surgery. The patient’s hemoglobin level did not change, and direct Coombs test performed daily was consistently negative. Anti-B titer was observed at a maximum of 1/8. The patient was followed up during the first year. This case of ILT from a cadaveric donor is significant because the 2.5-year-old recipient did not experience any complications after undergoing routine immunosuppressive treatment.